Penerapan Prinsip Partisipasi Dan Responsibilitas Dalam Proses Pembangunan Desa Di Desa Gattareng Kecamatan Pujananting Kabupaten Barru - Riantari, Misbah; Mappamiring, Mappamiring; Muhiddin, Amir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this study was to find out the application of the principles of participation and responsibility in the village development process in Gattareng Village, Pujananting District, Barru Regency which focused on the application of the principles of participation and responsibility in development. This study used descriptive qualitative research. Data collection techniques used the method of observation, interviews, and documentation. The results of this study showed that the application of the principles of participation and responsibility in the village development process had been said to be successful in making decisions related to development such as attendance at meetings, contributions of thoughts such as ideas or suggestions conveyed and a good response from the community, but more efforts were still needed  from the village government and village officials as well as the local community related to participation and responsibility in village development. In the village development process, there were several obstacles, namely the lack of public awareness of human resources, community activities, internal and external factors and coordination between the government and the community.Keywords: The principle of participation, responsibility, village development.